Immunomodulation by gastrointestinal carbon black nanoparticle exposure in ovalbumin T cell receptor transgenic mice. Issue 10 (25th November 2016) - Fine, Jason H.; Bondy, Genevieve S.; Coady, Laurie; Pearce, Bevan; Ross, Nikia; Tayabali, Azam F.; Halappanavar, Sabina; Caldwell, Don; Curran, Ivan; Lefebvre, David E.
Abstract: Humans could become exposed to carbon black nanoparticles (CBNPs) in consumer products or an occupational setting. In rodent models, acute respiratory, subcutaneous, and direct immune cell exposure to CBNPs has been shown to enhance allergic sensitization to co-administered ovalbumin (OVA) protein from chicken egg. However, little is known about the effects of ingested CBNPs on immunological responses and oral tolerance to food antigens. We hypothesized that ingestion of CBNPs would enhance the development of food allergy to OVA. Allergy prone DO11.10 mice were orally exposed to CBNPs every second day for 2 weeks (total dose 10.8 (LOW) or 108 μg (HI)), with and without (±) co-administered OVA. Systemic immune parameters were measured at necropsy. Exposure to OVA resulted in significant increases in serum anti-OVA IgG1, anti-OVA IgM, and anti-OVA IgA antibodies relative to vehicle control. Immunophenotyping revealed a reduction in the number of OVA-specific CD4 +  T helper cells upon OVA ± CBNP HI treatment in the spleen. Yet, secretion of the allergy-associated Th2 cytokines IL-4, IL-9, and IL-13 was greater in OVA323-339 peptide-pulsed splenocytes from OVA + CBNP HI -treated mice compared with control. Transcriptome analysis at necropsy of splenocytes from OVA + CBNP HI dose mice compared with OVA mice revealed increases in the allergy associated genes Il4 and Stat6 and decreases in Csf3r and Retnlg . Although oral exposure to high-dose CBNPs did not impact OVA-specific antibody production relative to OVA, we did observe increased expression of genes and cytokines associated with allergy in peripheral splenocytes. This work suggests that CBNP gastrointestinal exposure may potentiate allergy pathways.